Antihypertensive drug use and blood pressure control among stroke survivors in the United States: NHANES 2003‐2014. Issue 6 (17th May 2019) - Sonawane, Kalyani; Zhu, Yenan; Balkrishnan, Rajesh; Suk, Ryan; Sharrief, Anjail; Deshmukh, Ashish A.; Aguilar, David
Abstract: Understanding the patterns of antihypertensive drug use and blood pressure (BP) control among stroke survivors in the "real‐world" setting is important to identify gaps in treatment and control, if any. The objective of our study was to assess trends and patterns in antihypertensive drug use and BP control among stroke survivors in the United States. We performed a retrospective cross‐sectional analysis of the 2003‐2014 National Health and Nutrition Examination Survey (NHANES). Stroke and hypertension diagnoses were self‐reported. Information regarding the use of antihypertensive drugs was collected during an in‐person interview. Measurement of BP was performed by trained medical professionals in mobile examination centers. A total 1244 adult stroke survivors (equating to 6 232 215 stroke survivors nationwide) were identified, of which 956 had hypertension. Antihypertensive drug use increased from 2003 (79.5%) to 2014 (92.2%; P for trend < 0.001). The prevalence of drug use was lower (52%) among survivors aged 20‐39 years compared with older age groups. Use of ≥2 antihypertensive drugs was prevalent (63.8%), but diuretics alone or in combination with angiotensin‐converting enzyme inhibitors were underutilized (22.4%). More than one‐third of the survivors were not at BP goal (ie, BP < 140/90 mm Hg). Males were more likely to attain BP goal than female stroke survivors (odds ratio [OR] = 2.02; 95% CI: 1.34‐3.05). Our findings suggest that despite improvements in antihypertensive drug use in the recent years, BP is not adequately controlled in a significant proportion of stroke survivors. Further research focusing on understanding the reasons for unmet BP goal in stroke survivors is needed.